Effects of early nutritional intervention by a nutritional support team for patients with head and neck cancer undergoing chemoradiotherapy or radiotherapy. Issue 2 (5th October 2020) - Kono, Michihisa; Wakisaka, Risa; Kumai, Takumi; Hayashi, Ryusuke; Komatsuda, Hiroki; Sato, Ryosuke; Abe, Yasushi; Yamaki, Hidekiyo; Takahara, Miki; Katada, Akihiro; Hayashi, Tatsuya; Harabuchi, Yasuaki
Abstract: Background: We analyzed the effects of early nutritional intervention by a nutritional support team (NST) in patients with head and neck squamous cell carcinoma (HNSCC) undergoing chemoradiotherapy or radiotherapy. Methods: This study investigated whether early nutritional interventions by a multidisciplinary NST improve body weight loss, mucositis, serum albumin level, and hospital length of stay. Results: Sixty‐one patients with HNSCC were treated during the study, and 32 patients received NST intervention since admission. The median weight loss rates were 3.3% and 7.3% and grade 3 mucositis was observed in 25.0% and 70.0% of patients in the intervention and nonintervention groups, respectively. In the intervention group, serum albumin level through treatment increased and the hospital length of stay from the end of treatment was shortened. Conclusion: Early nutritional intervention by a multidisciplinary NST improved body weight loss rate, mucositis, albumin level, and hospital length of stay, which might lead to better clinical outcomes.